Improving Brand Trust Through the Creation of a Landing Page Using React for PT Haebot Teknologi Indonesia Blitar - Aldio Fernanda; Joni Dwi Pribadi; Tri Ramadani Arjo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study investigates a B2B brand trust deficit at PT Haebot Teknologi Indonesia, a provider of specialized CNC machinery, stemming from a fragmented digital presence on B2C-oriented platforms that failed to communicate technical expertise and provide transactional assurances. Using a two-cycle action research methodology, a professional, long-form sales landing page was developed using the React framework to serve as a centralized, authoritative digital asset. The intervention's effectiveness was evaluated using a purpose-built questionnaire administered to 15 stakeholders. The initial cycle revealed a critical paradox, while aesthetic and identity-based signals (Authenticity, Consistency) were successfully established, the intervention failed to build foundational trust due to the absence of explicit warranty and risk information. The second cycle rectified these deficits by adding an after-sales policy section and product-level risk warnings. Post-intervention analysis showed that the previously weakest pillars, Transparency and Reliability, improved to perfect mean and median scores of 1.0. The study's primary contribution is a proposed hierarchical model of B2B digital trust, suggesting that for a technical audience, transactional assurances that mitigate risk function as a prerequisite for trust, rather than as an additive component. Their absence appears to constitute a functional veto that nullifies the positive effect of other brand-building signals.